A review of problems of bacterial biofilm on contact lenses (World Journal of Experimental Biosciences, 2025)
Contact lenses are a widely used and effective means of vision correction, offering relief to around the world use contact lenses. But these lenses can sometimes get colonized by microorganisms, which might lead to infections and inflammation on the eye’s surface. A major concern in this context is the formation of bacterial biofilms on contact lenses, which can cause significant complications, including ocular discomfort and more serious eye conditions. This study aims to discuss how bacterial biofilms can cause eye infections related to contact lenses. Without proper treatment, these infections can lead to vision loss or, in severe cases, loss of the eye. In conclusion, biofilms are a key factor contributing to contact lens-related ocular infections and inflammation.